KNOWLEDGE AND AWARENESS OF VITAMIN D DEFICIENCY AMONG THE GENERAL POPULATION IN SAUDI ARABIA (CAHIERS MAGELLANES-NS, 2024)
Background: Vitamin D deficiency is a common problem worldwide, during the past decade, Vitamin D status has been a major concern. Numerous variables, including inadequate dietary vitamin D, malabsorption, and poor utilization, as well as increased needs, increased excretion, and catabolism, can contribute to vitamin D insufficiency. In addition, there are a variety of diseases that impair the bioavailability of vitamin D, such as gastrointestinal issues that restrict absorption and liver and kidney issues that can prevent the activation of parenteral vitamin D or interfere with its conversion to active metabolites. Lack of vitamin D is linked to autoimmune conditions like multiple sclerosis and rheumatoid arthritis. Objectives: the study aimed to assess the level of knowledge and awareness level of vitamin D deficiency among the general population of Saudi Arabia. Methodology: A cross-sectional study design was employed. A self-administered questionnaire was administered to an adult sample of 384 participants seeking information on their knowledge about vitamin D.  Data was subsequently transmitted to the SPSS, version 20 (IBM SPSS Statistics for Windows, Version 20.0, Armonk, NY: IBM Corp.). Results: the total sample size is 375 individuals 189 males, 186 females. As regard knowledge and awareness score, 32.8% demonstrated a low level of knowledge about vitamin D deficiency. Conversely, 143 participants, comprising 38.1% of the sample, exhibited a moderate level of knowledge, while 29.1% of the respondents showed a high level of awareness. Comparison of knowledge scores among sociodemographic groups revealed significant differences in knowledge scores for age while no significant relation to nationality, education level, gender, family income and marital status. Conclusion: The study highlighted a fair level of knowledge regarding vitamin D deficiency among study participants. There is a significant association between level of knowledge and age. More campaigns need to be held to educate people sufficiently regarding the dietary sources and established health benefits of vitamin D for bones, muscles, and immune system. Nongovernment organizations and social workers may work together with government health-care organizations to teach parents and children about the uses and benefits of vitamin D.